Joschka Fischer and the making of the Berlin Republic : an alternative history of postwar Germany - Hockenos, Paul, 1963- (Oxford University Press, 2008)
Preface. Introduction/Prologue. Part I: Adenauer's Germany. 1. Postwar. 2. The Silent Fifties. Part II: The Red Decade. 3. Old Left - New Left. 4. The Radical Left. Part III: From Protest to Parliament. 5. Siezing the Initiative. 6. Going Realo. 7. Autumn of the Euromissiles. 8. One Two Many Germanys. Part IV: The Berlin Republic. 9. Answering German Questions. 10. The Price of Power. 11. Continential Drift. Conclusion.